2006
DOI: 10.1186/1745-6215-7-35
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety of rosuvastatin 10 mg and atorvastatin 20 mg in high-risk patients with hypercholesterolemia – Prospective study to evaluate the Use of Low doses of the Statins Atorvastatin and Rosuvastatin (PULSAR)

Abstract: Background: Many patients at high risk of cardiovascular disease do not achieve recommended low-density lipoprotein cholesterol (LDL-C) goals. This study compared the efficacy and safety of low doses of rosuvastatin (10 mg) and atorvastatin (20 mg) in high-risk patients with hypercholesterolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
40
7
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 47 publications
13
40
7
9
Order By: Relevance
“…13 Michael et al showed reduction in HDL (40%) more in Atorvastatin and Fibrate combination than in Atorvastatin monotherapy. 12 This is similar to our result (3%, P <0.0001) in lowering HDL in Group I (Atorvatatin) vs Group III (Atorvastatin and Fibrate).…”
Section: -8supporting
confidence: 81%
See 1 more Smart Citation
“…13 Michael et al showed reduction in HDL (40%) more in Atorvastatin and Fibrate combination than in Atorvastatin monotherapy. 12 This is similar to our result (3%, P <0.0001) in lowering HDL in Group I (Atorvatatin) vs Group III (Atorvastatin and Fibrate).…”
Section: -8supporting
confidence: 81%
“…This is similar to Eliasson et al 11 Rosuvastatin 67%, Clearfield et al 12 (Rosuvastatin 10 mg reduced LDL-C levels significantly more than atorvastatin 20 mg at week 6 (44.6% vs. 42.7%, P <0.05). 11,12 In our result Atorvastatin with Fibrates was better than Atorvastatin monotherapy in decreasing LDL (34.66% vs 33.85%) our result was similar to the results of Karalis et al (33% vs 35%). 13 Michael et al showed reduction in HDL (40%) more in Atorvastatin and Fibrate combination than in Atorvastatin monotherapy.…”
Section: -8supporting
confidence: 77%
“…More than 90% of the patients achieved their target LDL goal in both groups, which is higher than the rate reported in a previous report on patients with a different ethnic background 32) , perhaps because, in our study, the baseline LDL levels were not high and remained well controlled with conventional doses of both statins. We also confirmed that the administration of cilostazol therapy in addition to a statin had favorable effects on the HDL and triglyceride profiles, as suggested by previous studies 33,34) .…”
Section: Discussioncontrasting
confidence: 50%
“…С целью изучения липидмодулирующих возможностей последнего было выполнено большое количество исследований, пре-паратом сравнения в рамках которых достаточно часто выступал аторвастатин [7][8][9][10][11][12][13]. В большинстве подобных исследований розувастатин несколько пре-восходил аторвастатин во влиянии на уровень ХС-ЛПНП [7][8][9][10][11]. Однако в ряде исследований достовер-ных различий при сравнении отдельных доз аторва-статина и розувастатина не отмечалось.…”
Section: аторвастатин -20 лет в борьбе за жизньunclassified